The Relationship between Corporate Governance and Return: An Empirical Study of the Listed Companies in the Stock Exchange of Thailand in the SET 100 Index - Silapamahabandit, Kitikun; Hensawang, Surang (Rajapark Journal, 2020)
The literature on the relationship between corporate governance and firm value has widely been found. However, the firm value in terms of return which is considered beneficial to investors has been limited. Thus, this research examines such relationships using the companies listed in the Stock Exchange of Thailand in the SET 100 Index. Corporate governance is measured by the number of board of directors, the number of board of directors’ meeting, the proportion of top executives to the board of directors, the proportion of independent directors to the board of directors, and the amount of board of directors’ compensation. In addition, the dividend-adjusted return is analyzed. Multiple linear regression is estimated to examine such a relationship. A significant positive relationship between the number of board of directors’ meeting and return is found. On the other hand, a significant negative relationship related to the amount of board of directors’ compensation is evident. In addition, the insignificant relationships of the proportion of top executives to the board of directors, the proportion of independent directors to the board of directors, and the number of board of directors are showed. It is suggested that an investor should consider the firm with a high number of board meetings and a low amount of board member compensation, and the company itself should find new forms of compensation rather than cash benefits.